AN EXAMINATION OF HERDING BEHAVIOR ON THE STOCK MARKET: AN HALAL PERSPECTIVE - Dewi Suryani Sentosa (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2023)
The objective of this study is to examine herding on the stock market from a halal perspective for understanding the way of thought and it could result in the right decision for investors. The decision can be obtained from herding which is seen as a factor of the stock market being more volatile and risky. This behavior is done by the investor due to feeling doubt in choosing a stock because there are no other choices to make some decisions and they assume that other investors have some information. On the other hand, herding can affect the level of risk to be faced. The problems being analyzed are; First, how the halal perspective about herding behavior. Second, what are the criteria for herding based on the halal perspective? This study was written over a month beginning in August 2018. The primary data is mainly gathered from Al-Qur’an, al Hadits, and Ushul Fiqh. To support the data, an in-depth analysis technique was also used. In addition, secondary data from journal articles, books, and other related kinds of literature were also utilized. This paper is using the descriptive method of analysis, and include in the literature research category. The findings show that herding from a halal perspective is allowed but it must be following the knowledge of stock analysis and who person they follow. It could not be followed blindly to result in a decision. This study would make Syariah economics has the potential to answer the shortcoming found in the phenomenon of the stock market.